2017
DOI: 10.13102/sociobiology.v64i4.1153
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Position of the Western Bangladesh Populations of Weaver Ant, Oecophylla smaragdina (Fabricius) (Hymenoptera, Formicidae)

Abstract: Weaver ant, Oecophylla smaragdina is distributed from India through SE Asia to North Australia including many tropical western pacific Islands. A recent phylogenetic study of O. smaragdina revealed the central Bangladesh population as SE Asian mainland clade despite of its geographical proximity to India. However, the sample analyzed was limited and the geographical border between the two groups has not been presented. In this study, several samples collected from western parts of Bangladesh have been used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…They suggested a contraction-expansion scenario during climatic oscillation leads to geographical overlaps of two mtDNA clades created the allopatric population of Asian elephants in India, Sri Lanka and Myanmar. In the case of weaver ant in Bangladesh, as both the Indian and SE Asian types were dominated in Western and Eastern part of the country, respectively and there was not such a big border of separating those two populations (Rahman et al 2017a).…”
Section: Successful Detection Of Identical Allelementioning
confidence: 98%
See 1 more Smart Citation
“…They suggested a contraction-expansion scenario during climatic oscillation leads to geographical overlaps of two mtDNA clades created the allopatric population of Asian elephants in India, Sri Lanka and Myanmar. In the case of weaver ant in Bangladesh, as both the Indian and SE Asian types were dominated in Western and Eastern part of the country, respectively and there was not such a big border of separating those two populations (Rahman et al 2017a).…”
Section: Successful Detection Of Identical Allelementioning
confidence: 98%
“…The phylogenetic study of O. smaragdina based on mitochondrial Cytb and CO1 genes identified two major types where Indian types occurred mainly in India and Sri Lanka while the Southeast Asian (SE Asian) types have been observed in most of the SE Asian countries including Bangladesh (Azuma et al 2006(Azuma et al , 2002. However, recent phylogenetic study revealed the occurrence and dominancy of Indian type in the western part (Rahman et al 2017a) and SE Asian types in the eastern part and overlapping population of O. smaragdina in the central part of Bangladesh (Rahman et al 2017b) that can lead the chance of hybridization. Recently, for inferring the evidence of hybridization a comprehensive view of evolutionary history by analyzing nuclear and mitochondrial DNA between species level phylogeny in Hymenoptera was found effective and has been used extensively (Roos et al 2011;(Ascher et al 2001;Cameron and W illiams, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It might also affect the distribution of Oecophylla in different parts of the world. Lokkers Rahman et al, (2017a). They identified that the western Bangladesh population were mainly Indian type whereas the Eastern part was dominated by South East Asian type, although the middle part of the country were occupied by overlapping populations of both Indian and South East Asian type.…”
Section: Summary Of the Distribution Patternmentioning
confidence: 99%
“…Previous phylogeographic study on O. smaragdina based on mitochondrial Cytb and CO1 genes identified two major types where Indian types occurred mainly in India and Sri Lanka while the Southeast Asian (SE Asian) types have been observed in most of the SE Asian countries including Bangladesh (Azuma et al 2006). However, recent phylogenetic study revealed the occurrence and dominancy of Indian type in the western part (Rahman et al 2017b) and SE Asian types in the eastern part and overlapping population of O. smaragdina at the central part of Bangladesh (Rahman et al 2017a). In Bangladesh, the occurrence of different types implies the chance of hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the occurrence of Indian type from Bangladesh has been recorded (Rahman et al 2017b). The recent phylogenetic study based on mitochondrial CO1 and Cytbgenes revealed the overlapping distribution of both India and Southeast Asian clades of O. smaragdina in central Bangladesh (Rahman et al 2017a). In Bangladesh, the occurrence of different types implies the chance of hybridization.…”
Section: Introductionmentioning
confidence: 99%